Effect on consumers’ sustainable purchase intention of dietary supplement purine labeling - Yang, Dajun; Gui, Gui; Yao, Yisong; Ke, Xiong (Frontiers in Nutrition, 2025)
Previous studies have shown that nutritional labeling of dietary supplements plays a pivotal role in shaping consumer behavior. Nevertheless, few studies have focused on the relationship between purine labeling and consumers’ sustainable consumption intentions. To address this research gap, this study recruited 1,786 participants through six experiments to explore the effects of purine labeling on consumers’ sustainable purchase intentions, underlying mechanisms, and boundary conditions. The results showed that purine labeling significantly enhanced consumers’ intention to continue purchasing dietary supplements (Experiment 1); furthermore, health consciousness mediated the relationship between purine labeling and sustainable purchase intention (Experiment 2); further, the interaction between the threat of disease and purine label had significant effects on consumer sustainable purchasing (Experiment 3); finally, the moderating effect of fear of risk on the relationship between purine labeling and consumer sustainable purchase intention (Experiment 4). Immediately following this, this study demonstrated the mediating role of perceived gout susceptibility (Experiment 5) and the moderating role of the connection of nature (Experiment 6). The strengths of this study include its comprehensive approach, which consists of six experiments that explore the effects of purine labeling systematically. The large sample size and the use of mediation and moderation analyses provided robust evidence for the proposed relationships. However, this study also has some limitations, such as the generalizability of the findings being limited by the manipulated environment, the self-reported sustainable purchasing intention are biased, and the cross-sectional study not demonstrating how purchase intention changes over time. This study advances our understanding of the relationship between dietary supplement purine labeling and consumer purchase decisions and provides empirical support for marketing strategies, especially in health consciousness and environmental sustainability. In addition, this study provides new insights into how purine labeling further influences consumers’ purchase intentions through factors such as health consciousness disease threat and fear of risk, contributing to developing more effective labeling design and promotional strategies to promote sustainable consumer behavior.